INFLUENCE OF DIETARY BETAINE ON NUTRIENT UTILIZATION AND DIGESTIVE ENZYME ACTIVITY IN YELLOW-FEATHER BROILERS DURING STARTER PHASE - W.C. Liu; B.H. Ou; Y.L. Yuan; C.Y. Sun; M. Xiao; Z.H. Zhao; L.L. An (Journal of Animal and Plant Sciences, 2020)
The present experiment was conducted to investigate the effects of dietary supplementation with different levels of betaine on nutrient utilization and digestive enzyme activity in indigenous yellow-feather broilers during starter phase. A total of 288 male, one-d-old Huaixiang chickens with an average initial body weight (BW) of 44.52 ± 1.07 g were randomly allotted to 4 treatments. Each dietary treatment consisted of 6 replicates, with 12 birds per replicate. The 4 dietary treatments were corn-soybean meal-based diets and supplemented with 0, 500, 1000 and 2000 mg/kg betaine, respectively. The trial period lasted 28 d. It was found that dietary betaine supplementation improved the calcium (Ca) utilization (cubic, P=0.0187). Meanwhile, dietary supplementation with different levels of betaine increased the trypsin activity (quadratic, P=0.0445) and lipase activity (cubic, P=0.0344) of the jejunum. Taken together, this study revealed that betaine could promote the digestive function in indigenous yellow-feather broilers during starter phase.
Keywords: betaine; digestive function; indigenous yellow-feather broilers; starter phase